Scope and mechanistic insight into the chemistry of cyanocarbenes derived from alkynyl triazenes by UV irradiation - Maag, Melina; Dittmer, Linus Bjarne; Michel, Elena; Mackenroth, Alexandra; Dietl, Martin C.; Rominger, Frank; Rudolph, Matthias; Dreuw, Andreas; Hashmi, A. Stephen K. (Organic chemistry frontiers, 2024)
Herein we disclose a systematic evaluation of the scope and limitations for the use of alkynyl triazenes for the synthesis of cyano-substituted cyclopropanes and cyclopropenes. The method is based on the formation of a cyanocarbene by cleavage of the N1-N2 bond of the alkynyl triazene precursor under UV light, which then reacts with a styrene or alkyne to form the respective products, making this a simple approach avoiding metals typically used in related reactions of organic azides. Different substituents on the triazene moiety, N-terminus and styrene/alkyne were investigated concerning their influence on the yield and diastereoselectivity with respect to the resulting cyclopropanes. The study showed that electron-rich aryl substituents at the alkynyl triazenes enable a good diastereomeric excess favouring the anti-diastereomer. Accompanying computational studies revealed that this diastereomeric preference can be qualitatively predicted from the relative stability of the singlet and triplet states of the cyanocarbene, as well as the dispersive attraction between the carbene and the olefin.
Gesehen am 31.07.2025